Study of the mechanisms of crocetin‐induced differentiation and apoptosis in human acute promyelocytic leukemia cells. Issue 2 (11th September 2018) - Moradzadeh, Maliheh; Ghorbani, Ahmad; Erfanian, Saiedeh; Mohaddes, Seyedeh Tahereh; Rahimi, Hossein; karimiani, Ehsan Ghayoor; Mashkani, Baratali; Chiang, Shih‐Chieh; El‐Khamisy, Sherif F.; Tabarraei, Alijan; Sadeghnia, Hamid Reza
Abstract: Crocetin, the major carotenoid in saffron, exhibits potent anticancer effects. However, the antileukemic effects of crocetin are still unclear, especially in primary acute promyelocytic leukemia (APL) cells. In the current study, the potential antipromyelocytic leukemia activity of crocetin and the underlying molecular mechanisms were investigated. Crocetin (100 µM), like standard anti‐APL drugs, all‐trans retinoic acid (ATRA, 10 µM) and As2 O 3 (arsenic trioxide, 50 µM), significantly inhibited proliferation and induced apoptosis in primary APL cells, as well as NB4 and HL60 cells. The effect was associated with the decreased expressions of prosurvival genes Akt and BCL2, the multidrug resistance (MDR) proteins, ABCB1 and ABCC1 and the inhibition of tyrosyl‐DNA phosphodiesterase 1 (TDP1), while the expressions of proapoptotic genes CASP3, CASP9, and BAX/BCL2 ratio were significantly increased. In contrast, crocetin at relatively low concentration (10 µM), like ATRA (1 µM) and As 2 O 3 (0.5 µM), induced differentiation of leukemic cells toward granulocytic pattern, and increased the number of differentiated cells expressing CD11b and CD14, while the number of the immature cells expressing CD34 or CD33 was decreased. Furthermore, crocetin suppressed the expression of clinical marker promyelocytic leukemia/retinoic acid receptor‐α ( PML/RARα ) in NB4 and primary APL cells, and reduced the expression of histone deacetylase 1 ( HDAC1 ) in all leukemic cells. The results suggested that crocetin can be considered as a candidate for future preclinical and clinical trials of complementary APL treatment. Abstract : Schematic mechanism by which crocetin induces apoptosis and differentiation and inhibits TDP1 and MDR protein Crocetin inhibits proliferation and induces apoptosis in leukemic cells. Crocetin decreases expression multidrug resistance proteins and inhibits the activity of tyrosyl‐DNA phosphodiesterase 1 ( (TDP1) in leukemic cells. Crocetin induces differentiation of leukemic cells toward granulocytic pattern. Crocetin suppresses the expression of clinical marker promyelocytic leukemia/retinoic acid receptor‐α (PML/RARα) and reduces the expression of histone deacetylase 1 (HDAC1) in leukemic cells.